(untitled) (Journal of the College of Basic Education, 2022)
Al-As’ar Al-Ja’fi is a poet and knight who lived in the time of Imru’ Al-Qays bin Hajar Al-Kindi. He had only one poem, which was called Al-Maqsura, which pierced time with an inexhaustible glow. This study is an attempt to find out the relationship between the behavior of the assaar and its language. Perhaps the research clarifies the reasons for the saying and the linguistic behavior of the narrator through his poem. Since language is one of the most important manifestations of human behavior, linguists have studied this behavior in the discourse issued by the speaker representing the behavior, while psychologists have studied the behavior and its causes, interested in the reasons why the speaker chooses certain words over others, and how the addressees differ in their perception of the discourse or in their identification of the semantic features of the discourse. The study combined two approaches, one linguistic and the other psychological, and their fusion in one melting pot. This approach combines language and behavior as an attempt to explain the behavior of the speaker, on the basis of applying what the schools of psychology have revealed and applying them to the literary text, in order to reach an analysis of the writer’s psychology to know his personal characteristics, and the psychological complexes he suffered from; Because of the circumstances he went through in his life. We find everything that went through his life clear in his words as a bright image in his literary text and this is what we will address during the study. This study is applied in which I search for the unconscious implications of the poet and the pain of loss that caused him to suffer a decade, and what he endured from not taking his brothers to avenge their father, and predicting his personality and drawing it anew and making its physical structure through poetry